2008
DOI: 10.1002/fld.1805
|View full text |Cite
|
Sign up to set email alerts
|

Steady flow through a realistic human upper airway geometry

Abstract: SUMMARYAir flow through a human upper airway (central part) has been carried out using a realistic geometry. In addition to explaining the anatomy, problems and importance of patient-specific study of human upper airways, this article also presents some qualitative and quantitative simulation results. As expected, the shear and pressure forces are large in the oropharynx and laryngopharynx, where the flow passage is narrow. This clearly indicates that these locations should be the focus of any study aimed at u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 65 publications
1
34
0
Order By: Relevance
“…In [15] it is concluded that locations of narrow flow passage should be the focus of any study aiming at understanding the human upper airway collapse. The need for experimental validation of flow simulations is stressed in [17].…”
Section: Introductionmentioning
confidence: 98%
“…In [15] it is concluded that locations of narrow flow passage should be the focus of any study aiming at understanding the human upper airway collapse. The need for experimental validation of flow simulations is stressed in [17].…”
Section: Introductionmentioning
confidence: 98%
“…MRI measurements of steady flow in the proximal thoracic airways (de Rochefort et al 2007), Reynolds-averaged Navier-Stokes (RANS) simulation of the upper airways (Nithiarasu et al 2008) and large eddy simulation (LES) of steady flow from the mouth to the sixth generation ).…”
Section: Introductionmentioning
confidence: 99%
“…Noticeably, the present results are consistent with both experimental and CFD data published previously. 12,13 The effect of the glottic area on the maximum air velocity in the larynx with inlet velocity w = 0.169 m/s was also analyzed. For a given flow, mass flow rates through the various openings are identical.…”
Section: Resultsmentioning
confidence: 99%
“…The pressure drop is an important parameter, covered extensively in a number of papers that discuss airflow in the upper respiratory tract. [11][12][13][24][25][26] The calculations by means of the Fluid software yielded the values shifts toward larger values. Based on CFD analyses, it was possible to correlate ΔP with the area of the glottic opening.…”
Section: Discussionmentioning
confidence: 99%